Learning Musculoskeletal Imaging - Ribes, Ramón; Vilanova, Joan C. (Learning Imaging, 2010)
This introduction to musculoskeletal imaging is a further volume in the Learning Imaging series. Written in a user-friendly format, it takes into account that musculoskeletal radiology is a subspecialty which has widely expanded its scope and imaging capabilities with the advent of ultrasound, MRI, multidetector CT, and PET. The book is divided into ten sections covering: infection and arthritis, tumors, tendons and muscles, bone marrow, spine, shoulder, elbow, hand and wrist, hip and pelvis, knee, and ankle and foot. Each chapter is presented with an introduction and ten case studies with illustrations and comments from anatomical, physiopathological and radiological standpoints along with bibliographic recommendations. Learning Imaging is a unique case-based series for those in professional education in general and for physicians in particular.